Respuesta :
Answer:
-7
Step-by-step explanation:
first multiply 3 and 4 because PEMDAS
so it now looks like
12 - 9 - x = 10
now minus 12 and 9
3 - x = 10
move x to the other side by adding x to both sides
3 = 10 + x
and move 10 to the other side by subtracting 10 to both sides
3 - 10 = x
x = -7
now check
3*4 - 9 - (-7) = 10 ?
12 - 9 + 7 = 10 ?
3 + 7 = 10 ?
10 = 10
Step-by-step explanation:
[tex]3\cdot \:4+\left(-9\right)-x=10[/tex]
[tex]\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a[/tex]
[tex]3\cdot \:4-9-x=10[/tex]
[tex]\mathrm{Multiply\:the\:numbers:}\:3\cdot \:4=12[/tex]
[tex]12-9-x=10[/tex]
[tex]\mathrm{Subtract\:the\:numbers:}\:12-9=3[/tex]
[tex]-x+3=10[/tex]
[tex]\mathrm{Subtract\:}3\mathrm{\:from\:both\:sides}[/tex]
[tex]-x+3-3=10-3[/tex]
[tex]Simplify[/tex]
[tex]-x=7[/tex]
[tex]\mathrm{Divide\:both\:sides\:by\:}-1[/tex]
[tex]\frac{-x}{-1}=\frac{7}{-1}[/tex]
[tex]Simplify[/tex]
[tex]x=-7[/tex]